Environment-friendly sludge baking-free building block and preparation method thereof

By using alkali excitation technology and blast furnace slag, fly ash and other materials to regulate the gel phase structure, the problems of low sludge strength and high resolution rate of heavy metals in cement curing method are solved, and efficient curing and Environmentally friendly sludge resource utilization.

CN119390422APending Publication Date: 2025-02-07WUHAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411491357.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing sludge-free block technology, the cement curing method has the problem of low strength and high resolution rate of heavy metals, which leads to the ineffective curing of heavy metals in the sludge, which has potential secondary hazards.

Method used

Using alkali excitation technology, the silicon-aluminum ratio and microstructure of the gel phase are regulated through blast furnace slag, fly ash and enhancers. Based on the alkali excitation system, heavy metals are physically encapsulated, chemically bonded, and surface adsorption and cured to enhance the pollutants in the sludge. Consolidation effect.

Benefits of technology

The consolidation of pollutants in the silt is comprehensively strengthened, the strength and stability of silt-free burn-in blocks are improved, the resolution rate of heavy metals is reduced, and the resource utilization of silt is achieved that is environmentally friendly and energy-saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390422A_ABST
    Figure CN119390422A_ABST
Patent Text Reader

Abstract

The invention provides an environment-friendly sludge baking-free building block and a preparation method thereof, and belongs to the technical field of solid waste resource utilization, the environment-friendly sludge baking-free building block comprises, by weight, 30-60 parts of sludge, 30-50 parts of a cementing agent, 5-20 parts of an alkali activator, 2-10 parts of a reinforcing agent and 10-20 parts of water, the cementing agent comprises blast furnace slag and fly ash, the mass ratio of the blast furnace slag to the fly ash is (0.5-5): 1, and the mass ratio of the alkali activator to the reinforcing agent is (0.5-5): 1. The reinforcing agent comprises a phosphorus-based reinforcing agent and an aluminum-based reinforcing agent, and the mass ratio of the phosphorus-based reinforcing agent to the aluminum-based reinforcing agent is (0.8-1.2): 1. The silica-alumina ratio and the microstructure of the gel phase are regulated and controlled through the blast furnace slag, the fly ash and the reinforcing agent, heavy metal is cured through three curing mechanisms of physical packaging, chemical bonding and surface adsorption on the basis of an alkali excitation system, and consolidation of pollutants in the sludge is intensified in an all-around mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste resource utilization, and specifically to an environmentally friendly sludge unfired building block and a preparation method thereof. Background Art

[0002] Silt is produced in water pollution prevention and dredging projects, mainly composed of fine-grained soil. With the acceleration of urbanization, a large amount of sewage is directly discharged into lakes and rivers, exacerbating the accumulation of silt. Nearly 100 million tons of silt are produced worldwide every year. The large amount of silt storage not only occupies a large amount of land resources, but also easily causes serious secondary pollution to the environment. At present, the main methods of silt treatment include landfill, incineration, composting, and land reclamation, but these treatment methods do not prevent the pollution of silt well and also lose their resource attributes.

[0003] Silt solidification technology is mainly divided into two categories: thermal treatment solidification and chemical solidification. Among them, thermal treatment solidification mostly adopts sintering method, which consumes a lot of energy, increases costs and increases carbon emissions, which is not conducive to large-scale promotion and application. The chemical solidification method uses solidification materials to generate products with gelling properties to improve the strength of silt. It does not require high-temperature treatment, has low economic costs, and has a wider range of applications. The raw materials of unfired blocks are widely available, and have the characteristics of no sintering and no steaming. They are widely used in the wall material construction industry. Using silt as the raw material for unfired blocks can not only effectively save resources, reduce energy consumption and costs, but also absorb a large amount of silt and solve environmental pollution problems.

[0004] The existing sludge unfired block technology requires the addition of a large amount of cement, gypsum, quicklime and other hydraulic cementitious materials as curing agents, such as a reservoir sludge unfired brick and its preparation method (CN117185733A), a sludge unfired brick and its preparation method (CN103102133A). Cement solidification is a commonly used waste solidification technology, but there are problems such as low strength of cement-solidified sludge blocks and high heavy metal re-dissolution rate. The heavy metals in the sludge cannot be effectively solidified, and organic matter such as nitrogen and phosphorus can easily decompose under the action of microorganisms to release ammonia nitrogen, phosphorus and other pollutants in the water. The obtained sludge unfired blocks consume a large amount of existing resources, are costly, and have potential secondary hazards. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides an environmentally friendly sludge unfired building block and a preparation method thereof, aiming to solve the technical problems of low strength and high heavy metal re-dissolution rate of cement solidification method.

[0006] In the first aspect, an embodiment of the present application provides an environmentally friendly sludge unfired building block. Calculated by weight, the raw material components include 30 to 60 parts of sludge, 30 to 50 parts of binder, 5 to 20 parts of alkali activator, 2 to 10 parts of reinforcing agent and 10 to 20 parts of water. The binder includes blast furnace slag and fly ash, and the mass ratio of blast furnace slag and fly ash is (0.5 to 5): 1. The reinforcing agent includes a phosphorus-based reinforcing agent and an aluminum-based reinforcing agent, and the mass ratio of the phosphorus-based reinforcing agent to the aluminum-based reinforcing agent is (0.8 to 1.2): 1.

[0007] Preferably, the phosphorus-based enhancer is one or both of sodium tripolyphosphate and calcium dihydrogen phosphate. Preferably, the aluminum-based reinforcing agent includes one or both of sodium metaaluminate and aluminum phosphate.

[0008] Preferably, the main chemical components of the sludge powder include, by weight: 35-55 parts of SiO2, 15-25 parts of Al2O3, 10-20 parts of loss on ignition (LOI), 0-3 parts of K2O, 0-3 parts of CaO, and 0-3 parts of MgO.

[0009] Preferably, the alkali activator includes a strong alkali activator and a weak alkali activator. The strong alkali activator includes one or both of sodium hydroxide and potassium hydroxide, and the weak alkali activator includes one or both of water glass and potassium silicate.

[0010] Preferably, the fly ash is Class F fly ash, and its main chemical components, calculated by mass, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.

[0011] Preferably, the blast furnace slag is S95 grade powder, and its main chemical components include, by weight: 30-50 parts of CaO, 25-35 parts of SiO2, 10-20 parts of Al2O3, and 5-10 parts of MgO.

[0012] In a second aspect, the present application provides a method for preparing an environmentally friendly sludge unfired building block, comprising the following steps: S1. Pretreatment of raw materials: remove impurities from the sludge slurry and dry it to a moisture content of less than 5% to obtain dried sludge, and grind, shrink and homogenize the dried sludge to obtain sludge; S2, mixing of raw materials: mixing the sludge in step S1 with blast furnace slag and fly ash to obtain a precursor; S3, preparation of blank: mixing the precursor in step S2 with water, a reinforcing agent and an alkaline activator to obtain a blank; S4, molding and curing: the blank obtained in step S3 is pressed into shape, and after demoulding, it is cured at a set temperature to obtain a building block.

[0013] Preferably, the grinding conditions in step S1 are: a rotation speed of 600 to 1200 rpm and a grinding time of 0.5 to 6 minutes.

[0014] Preferably, the curing temperature in step S4 is 15°C to 90°C.

[0015] Different from the existing technical solutions, the beneficial effects of this application include: This application adopts alkali excitation technology to regulate the silicon-aluminum ratio and microstructure of the gel phase through blast furnace slag, fly ash and reinforcing agent. Based on the alkali excitation system, the heavy metals are solidified by three solidification mechanisms: physical encapsulation, chemical bonding, and surface adsorption, thereby comprehensively strengthening the consolidation of pollutants in the sludge. The phosphorus oxygen group in the phosphorus-based enhancer is a hexahedral structure with better spatial structural performance, and can balance the charge of the system, replace the silicon component of the silicon-aluminum network space structure, and form a stable space network gel, thereby enhancing the strength of the sludge unfired building block; the aluminum-based enhancer increases the Al / Si ratio of the gel phase, inducing the spatial network structure of the gel phase to transform into a zeolite-like molecular cage, thereby strengthening the resistance to large-volume heavy metal ions (Pb 2+ 、Zn 2+ , Mn 2+ Physical packaging performance, etc.

[0016] The organic matter in the sludge can also play a role in cross-linking and nucleation, strengthening the self-consolidation of the sludge in the unburned state, eliminating the need to add other curing agents, and shortening the preparation cycle by utilizing the characteristics of the alkali-activated system. During the unburned preparation process, the retained humic acid in the sludge can be converted into fulvic acid that is easily soluble in water and beneficial to the growth of crops in an alkaline system, and the prepared sludge unburned blocks are more environmentally friendly. This application uses an unburned process to save energy and avoid the generation of CO2 during the calcination of sludge. , dioxins, etc., with obvious environmental protection effects, and reducing production costs and consumption of natural resources. The unburned bricks prepared by the present application can be cured at room temperature and have the advantages of high early strength. The heavy metals and organic matter in the sludge are well cured under the alkali excitation system, which is environmentally friendly. It can be widely used in housing construction, water conservancy projects and other fields. The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification, and in order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 This is the SEM-EDS image of the sludge unfired block in Example 1. DETAILED DESCRIPTION

[0019] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0021] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0022] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0023] Cement solidification is a commonly used waste solidification technology, but it has problems such as low strength and high heavy metal re-dissolution rate. Heavy metals in sludge cannot be effectively solidified, and organic matter such as nitrogen and phosphorus are easily decomposed by microorganisms to release ammonia nitrogen, phosphorus and other pollutants in water bodies. The sludge unburned blocks produced consume a large amount of existing resources, are costly, and have potential secondary hazards.

[0024] In order to solve the technical problems of low strength and high heavy metal re-dissolution rate when sludge is solidified by cement solidification method, the present application provides an environmentally friendly sludge unfired building block and a preparation method thereof, wherein the silicon-aluminum ratio and microstructure of the gel phase are regulated by blast furnace slag, fly ash and reinforcing agent, and heavy metals are solidified by three solidification mechanisms of physical encapsulation, chemical bonding and surface adsorption based on an alkali-excited system, thereby comprehensively strengthening the consolidation of pollutants in the sludge.

[0025] In a first aspect, an embodiment of the present application provides an environmentally friendly sludge unfired building block. The raw material components, measured by weight, include 30 to 60 parts of sludge, 30 to 50 parts of binder, 5 to 20 parts of alkali activator, 2 to 10 parts of reinforcing agent and 10 to 20 parts of water. The binder includes blast furnace slag and fly ash, and the mass ratio of blast furnace slag and fly ash is (0.6 to 4.3): 1. The reinforcing agent includes a phosphorus-based reinforcing agent and an aluminum-based reinforcing agent, and the mass ratio of the phosphorus-based reinforcing agent to the aluminum-based reinforcing agent is (0.8 to 1.2): 1.

[0026] In the technical solution of this embodiment, blast furnace slag and fly ash belong to the category of micro-aggregates and have a nucleation effect, so that the hydration products are evenly distributed in the entire interface transition zone. There are also differences in particle grading between the two. Changing the ratio can improve the particle grading, improve the self-compacting system, and reduce the pore structure in the pressed blocks. Blast furnace slag and fly ash contain a large amount of amorphous silicon-aluminum components, which will depolymerize, reconstruct, and self-organize to form a (C, N)-ASH gel phase in an alkaline environment. By adjusting the ratio of the two, the Si / Al ratio, Ca / Si ratio, Na / Al ratio and other parameters can be changed to optimize the hydration rate and consolidation performance of the gel phase.

[0027] Blast furnace slag contains high concentrations of Mg. During the hydration process, Mg 2+ Will be like Al 3+ Replaces Si in sludge 4+ To promote the formation of NA(M)-SH gel phase, the interweaving of multiple gel phases makes the microstructure of the gel phase denser, which manifests itself macroscopically as a significant enhancement in the mechanical properties of the sludge unfired blocks.

[0028] By using alkali excitation technology, the humic acid retained in the sludge can be converted into fulvic acid that is easily soluble in water and beneficial to the growth of crops in an alkaline system. The prepared sludge unfired blocks are more environmentally friendly.

[0029] Preferably, the phosphorus-based enhancer is one or both of sodium tripolyphosphate and calcium dihydrogen phosphate.

[0030] Preferably, the aluminum-based reinforcing agent includes one or both of sodium metaaluminate and aluminum phosphate.

[0031] The addition of sodium tripolyphosphate and calcium dihydrogen phosphate reinforcing agents introduces phosphorus oxygen groups into the silicon-aluminum system, replaces silicon in situ, balances the negative charge carried by aluminum in the alkali-excited system, improves the heat resistance and durability of the gel phase, and enhances the environmental universality of the application of unfired blocks.

[0032] The addition of sodium aluminate and aluminum phosphate enhancers introduced exogenous active aluminum to increase the Al / Si ratio of the gel phase, inducing the spatial network structure of the gel phase to transform into a zeolite-like molecular cage, thus strengthening the resistance to large-volume heavy metal ions (Pb 2+ 、Zn 2+, Mn 2 + The high-valent metal cations are also more likely to coordinate with oxygen to form negatively charged groups to replace the aluminum oxide groups in situ, thereby enhancing the ability of the gel phase to chemically bond and solidify heavy metals.

[0033] At the same time, the addition of sodium aluminate and sodium tripolyphosphate can increase the amount of gel phase generated and induce a slight decrease in the silicon-aluminum ratio in the gel, promote the formation of zeolite molecular cages, and improve the physical consolidation of heavy metals in the system.

[0034] The compounded reinforcing agent also has a certain retarding and water-reducing effect. It can form a stable hydration film on the surface of the particles, effectively hindering the coagulation between the particles, making the hydration process more uniform, and forming a network space structure with a higher degree of cross-linking and stronger adsorption and curing effects.

[0035] Preferably, the main chemical components of the sludge powder include, by weight: 35-55 parts of SiO2, 15-25 parts of Al2O3, 10-20 parts of loss on ignition (LOI), 0-3 parts of K2O, 0-3 parts of CaO, and 0-3 parts of MgO.

[0036] Preferably, the alkali activator includes a strong alkali activator and a weak alkali activator. The strong alkali activator includes one or both of sodium hydroxide and potassium hydroxide, and the weak alkali activator includes one or both of water glass and potassium silicate.

[0037] In the technical scheme of the embodiment of the present application, a strong base activator and a weak base activator are used in combination to provide a stronger alkalinity for the system, thereby promoting the rapid dissolution of active silicon and aluminum components in blast furnace slag and fly ash, and releasing metal cations such as sodium, potassium, and magnesium. The exogenous active silicon provided by the weak base activator and the metal cations released by the system will attack the bonded oxygen of the inert silicon-aluminum minerals in the sludge, reduce the binding energy of the silicon and aluminum bonds in the sludge, and achieve the synergistic activation of the sludge by blast furnace slag and fly ash, so that the silicon-aluminum minerals in the sludge are rapidly dissolved, and the secondary hydration of aluminum and silicon monomers participates in the composition of the gel phase, so that fly ash, blast furnace slag, and sludge synergistically participate in the hydration and cementation reaction, and achieve rapid self-consolidation of the sludge in a non-burning state, eliminating the need for the addition of cement curing agent.

[0038] Preferably, the fly ash is Class F fly ash, and its main chemical components, calculated by mass, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.

[0039] Preferably, the blast furnace slag is S95 grade powder, and its main chemical components include, by weight: 30-50 parts of CaO, 25-35 parts of SiO2, 10-20 parts of Al2O3, and 5-10 parts of MgO.

[0040] In a second aspect, the present application provides a method for preparing an environmentally friendly sludge unfired building block, comprising the following steps: S1. Pretreatment of raw materials: remove impurities from the sludge slurry and dry it to a moisture content of less than 5% to obtain dried sludge, and grind, shrink and homogenize the dried sludge to obtain sludge; S2, mixing of raw materials: mixing the sludge in step S1 with blast furnace slag and fly ash to obtain a precursor; S3, preparation of blank: mixing the precursor in step S2 with water, a reinforcing agent and an alkaline activator to obtain a blank; S4, molding and curing: using a hydraulic testing machine to press the blank obtained in step S3 into shape, and after demolding, curing at a set temperature for 7 days to obtain a building block.

[0041] Preferably, in step S1, a vibration grinder is used for grinding, the rotation speed is 600-1200 rpm, and the grinding time is 0.5-6 minutes.

[0042] Preferably, the curing temperature in step S4 is 15°C to 90°C.

[0043] Preferably, the pressure of the pressing molding in step S4 is 10-20 MPa, and the holding time is 1 min.

[0044] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0045] 1. Preparation method Example 1 Embodiment 1 provides a sludge unfired building block and a preparation method thereof, comprising the following steps: S1. Pretreatment of raw materials: remove impurities from the sludge and dry it to a moisture content of less than 5%, grind it with a vibration grinder at a speed of 800 rpm for 0.5 minutes, and reduce and homogenize the powder obtained by the quartering method and bag it for later use; S2, mixing of raw materials: mixing sludge powder with blast furnace slag and fly ash to obtain a precursor, the mass parts of each component are: 60 parts of sludge powder, 25 parts of blast furnace slag, and 15 parts of fly ash; S3, preparation of blank: the precursor is mixed with water, sodium hydroxide and water glass to obtain a blank, and the mass fraction of each component in the precursor is: 15 parts of water, 3.8 parts of sodium hydroxide, 5.8 parts of water glass, and 4 parts of a reinforcing agent prepared by mixing sodium tripolyphosphate and sodium aluminate in a ratio of 1:1; S4. Forming and curing: the blank is filled into a steel mold, and a hydraulic testing machine is used to form the blank under a pressure of 20 MPa for 1 minute, and the blank is demoulded and cured at 60°C for 7 days to obtain the final product.

[0046] Example 2 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S3 are: 15 parts of water, 7.6 parts of sodium hydroxide, 5.8 parts of water glass, and 4 parts of a reinforcing agent prepared by mixing sodium tripolyphosphate and sodium aluminate in a ratio of 1:1.

[0047] Example 3 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof in this embodiment, the mass fractions of the components in step S2 are: 60 parts of sludge powder, 15 parts of blast furnace slag, and 25 parts of fly ash.

[0048] Example 4 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S2 are: 60 parts of sludge powder, 32.5 parts of blast furnace slag, and 7.5 parts of fly ash.

[0049] Example 5 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S3 to the precursor are: 15 parts of water, 5.8 parts of sodium hydroxide, 5.8 parts of water glass, and 2 parts of a reinforcing agent prepared by mixing sodium tripolyphosphate and sodium aluminate in a ratio of 1:1.

[0050] Example 6 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S3 to the precursor are: 15 parts of water, 5.8 parts of sodium hydroxide, 5.8 parts of water glass, and 6 parts of a reinforcing agent prepared by mixing sodium tripolyphosphate and sodium aluminate in a ratio of 1:1.

[0051] Comparative Example 1 The difference between this comparative example and Example 1 is that: in the sludge unfired building block and the preparation method thereof of this comparative example, water glass is not added in step S3.

[0052] Comparative Example 2 The difference between this comparative example and Example 1 is that in the sludge unfired building blocks and the preparation method thereof of this comparative example, no sodium hydroxide is added in step S3.

[0053] Comparative Example 3 The difference between this comparative example and Example 1 is that: in the sludge unfired building blocks and preparation method thereof of this comparative example, the mass fractions of the components in step S2 are: 60 parts of sludge powder, 40 parts of blast furnace slag, and no fly ash is added.

[0054] Comparative Example 4 The difference between this comparative example and Example 1 is that: in the sludge unfired building blocks and preparation method thereof of this comparative example, the mass fractions of the components in step S2 are: 60 parts of sludge powder, 40 parts of fly ash, and no blast furnace slag is added.

[0055] Comparative Example 5 The difference between this comparative example and Example 1 is that in the sludge unfired building block and the preparation method thereof of this comparative example, no reinforcing agent is added in step S3.

[0056] Comparative Example 6 The difference between this comparative example and Example 1 is that in the sludge unfired building blocks and preparation method thereof of this comparative example, the 4 parts of reinforcing agent added in step S3 are single sodium tripolyphosphate and do not contain sodium aluminate.

[0057] Comparative Example 7 The difference between this comparative example and Example 1 is that in the sludge unfired building blocks and preparation method thereof of this comparative example, the 4 parts of reinforcing agent added in step S3 are sodium aluminate alone, and do not contain sodium tripolyphosphate.

[0058] 2. Test Method 1. Compressive strength test of silt unfired blocks After the blocks are cured to the specified age, the surface is wiped dry and tested by a press machine according to GB / T4111-2013 "Test Methods for Concrete Blocks and Bricks". Before testing the specimen, the press machine test bench needs to be cleaned, and the side of the specimen is used as the load-bearing surface to ensure that the specimen is placed in the center of the press machine workbench. The loading speed is maintained at 1kN / s throughout the test, and the press machine is started until the specimen is destroyed. The compressive strength calculation formula is:

[0059] In the formula R c is the compressive strength of the specimen, MPa, accurate to 0.1MPa; F c is the specimen failure load, kN; A is the pressure bearing area of ​​the specimen, m 2 .

[0060] 2. Flexural strength test of silt unfired blocks The flexural strength of the unfired blocks is tested by a press machine according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", with a loading speed of 0.08MPa / s. If the fracture position of the lower edge of the block is between the two concentrated load action lines, the flexural strength of the specimen is f f (MPa) The calculation formula for flexural strength is:

[0061] Where: f f is the flexural strength of concrete (MPa), the calculation result should be accurate to 0.1MPa; F is the specimen failure load (N); l is the span between supports (mm); b is the cross-sectional width of the specimen (mm); h is the specimen section height (mm).

[0062] 3. Water absorption test of silt unfired blocks The water absorption rate of unfired bricks is determined in accordance with GB / T4111-2013 "Test methods for concrete bricks and bricks". The test steps are as follows: (1) Randomly select three unfired bricks that have been cured and use a brush to clean the pores and cracks in the bricks; (2) Place the test piece in a water tank at 20±5℃. The bricks should be laid flat on the bottom of the box and cannot be stacked. The water level in the box should be at least 20mm higher than the bricks. After soaking for 24 hours, take out the bricks and wipe off the surface moisture. Weigh the saturated surface dry mass of the bricks at this time; (3) After the mass is weighed, place the bricks in a drying oven and dry them at 100±5℃ for 24 hours. Then weigh them every 2 hours until the difference between the two weighings is less than 0.2% of the last weighing. Cool the bricks to 20℃ in the drying oven and weigh the absolute dry mass at this time. The water absorption rate is calculated as follows:

[0063] Where: W24 is the water absorption rate of the sample after immersion for 24 hours, %; G0 is the mass of the sample in dry state, g; G24 is the mass of the sample after immersion in water for 24 hours, g.

[0064] 4. Softening coefficient test of silt unfired blocks The softening performance of unfired blocks is tested in accordance with GB / T4111-2013 "Test methods for concrete blocks and bricks". The experimental steps are as follows: (1) Select 10 bricks from the cured bricks and divide them into two groups. Wipe the surface of the bricks clean; (2) Randomly select a group of bricks and put them into a 20±5℃ water tank and soak them for 1 hour. The bricks are laid flat on the bottom of the box and cannot be stacked. The water surface is 20mm higher than the bricks. The other group of bricks is placed in a room with a room temperature of 20±5℃ and a relative humidity of 50±15% for curing; (3) After 1 hour, take out the bricks from the water tank, place them on an iron rack to control the moisture, and then test the compressive strength of the bricks with the other group of bricks according to the compressive strength test method. The calculation formula for the brick softening coefficient is:

[0065] Where: K is the softening coefficient, accurate to 0.01; P i is the compressive strength of water-immersed unfired brick, MPa; P 0 is the compressive strength of unfired bricks without water immersion, MPa.

[0066] III. Analysis of test results of various embodiments and comparative examples (1) Figure 1 This is the SEM-EDS image of the sludge unfired block in Example 1 of the present application. From the SEM photo, it can be seen that the prepared unfired block has a dense structure, and a large amount of gel phase is generated to cement the raw material particles together, and there are no obvious structural defects such as pores and cracks. The energy spectrum scan results show that the elements Si, Al, Na, Ca, and O show the characteristics of synchronous distribution, indicating that the main composition of the gel phase is (N, C)-ASH, and the hybrid symbiosis of sodium and calcium gel makes the gel phase more dense.

[0067] (2) According to the methods in Examples 1 to 5 and Comparative Examples 1 to 5, sludge unfired blocks were prepared, and the compressive strength, flexural strength, water absorption rate and softening coefficient of the blocks were tested. The test results are shown in Table 1 below: Table 1 Performance test results of sludge unfired blocks prepared in different embodiments and comparative examples

[0068] It can be seen from Example 1 that the 7d compressive strength of the sludge unfired bricks prepared by the method of the present application is up to 37.3 MPa, and all performances meet the standard of the highest grade MU25 in "JC / T 422-2007 Non-sintered Waste Tailings Bricks".

[0069] Examples 1-2 and Comparative Examples 1-2 show the effects of the type and amount of activators on the performance of building blocks: agents such as sodium hydroxide and potassium hydroxide can provide a strong alkaline environment for the system and are initiators of the hydration reaction of the gel phase; agents such as sodium silicate and potassium silicate provide weak alkalinity and cannot dissolve the active components quickly, but can act as exogenous active silicon to regulate the Si / Al ratio of the gel phase and increase the amount of gel phase generated; the combined use of sodium hydroxide and water glass provides a strong alkalinity for the system, which promotes the rapid dissolution of active silicon and aluminum components, and releases metal cations such as sodium, potassium, and magnesium. The exogenous and released large amounts of metal cations will attack the silicon and aluminum components in the sludge, reduce the binding energy of the chemical bonds, and achieve the synergistic activation of the sludge by blast furnace slag and fly ash under the alkaline activation system. The introduced exogenous silicon also makes the microstructure of the gel phase more compact, and the compression and flexural properties of the building blocks are improved.

[0070] Examples 3-4 and Comparative Examples 3-4 show the effect of the ratio of fly ash to blast furnace slag on the performance of the block: when the fly ash content is too small, the aluminum component in the alkali-activated system is low, the Si / Al ratio deviates from the optimal range, the three-dimensional network structure of the gel is unstable, and the performance of the sludge-free fired block decreases; when the blast furnace slag content is too small, the calcium and magnesium components in the system are reduced, and calcium can accelerate the hardening of the slurry by providing nucleation sites for the hydration products, and Ca 2+ Will react with [SiO4] in the system 4- and [AlO4] 5- Combined to form CSH or C-(A)-SH gel enriches the gel phase of the alkali-activated system, while Mg 2+ During the hydration process, it will react like Al 3+ Replace Si 4+ To promote the formation of NA(M)-SH gel phase. The appropriate ratio of fly ash and blast furnace slag can form a multi-gel symbiotic, stable and dense microstructure, and the performance of the block is enhanced.

[0071] Examples 5-6 and Comparative Example 5 show the effect of the amount of reinforcing agent on the performance of the building block: the addition of an appropriate amount of sodium aluminate and sodium tripolyphosphate can increase the amount of gel phase generated and induce a slight decrease in the silicon-aluminum ratio in the gel, promoting the formation of zeolite molecular cages. The compound reinforcing agent also has a certain slow setting and water-reducing effect, can form a stable hydration film on the surface of the particles, effectively hinders the coagulation between particles, makes the hydration process more uniform, and forms a network space structure with a higher degree of cross-linking, with stronger adsorption and curing effects, and the stability of the building block is enhanced. Less reinforcing agent is not enough to evenly coat the surface of the particles, and the synergistic activation effect cannot be achieved. Excessive reinforcing agent introduces a large number of charged groups, accelerates the coagulation speed of the gel phase, the hydration reaction is not sufficient, and the performance of the building block is reduced.

[0072] Comparative Examples 6-7 show the influence of the phosphorus component and the aluminum component in the reinforcing agent on the performance of the building block: the phosphorus oxygen group introduced by the phosphorus-based reinforcing agent preferentially replaces the silicon component of the silicon-aluminum network space structure, which does not significantly increase the gel phase content in the building block. However, the phosphorus oxygen group is a hexahedral structure, has better spatial structure performance, and can balance the charge of the system to form a stable spatial network gel. The aluminum oxygen group introduced by the aluminum-based reinforcing agent can fully participate in the composition of the gel phase, enhance the amount of gel phase generated in the building block, and significantly improve the compressive strength of the building block.

[0073] (3) The heavy metal element content in the building blocks of Example 1 and the heavy metal element concentration in the leachate were tested, and the test results are shown in Table 2 below: Table 2 Heavy metal element concentrations and standard limits in leachate element Content of heavy metal elements in building blocks (mg / L) Example 1 Heavy metal concentration of leachate (mg / L) Heavy metal concentration of leachate in comparative example 6 (mg / L) Comparative Example 7 Heavy metal concentration in leachate (mg / L) Standard limit (mg / L) Hg - - - - 0.00005 As - - - - 0.005 Cu 67.25 - 0.023 - 0.01 Cd - - - - 0.0001 Pb 249.49 - - 2.58 0.05 Zn 101.43 0.045 0.069 1.73 0.05 Cr 121.55 - - 0.002 0.005 Ni 12.91 - - - 0.005 As can be seen from Table 2, the sludge unburned blocks prepared according to the method in Example 1 meet the "Hazardous Waste Identification Standard-Leaching Toxicity Identification" (GB 5085.3-2007), and the leachate meets the "Groundwater Quality Standard" (GB 14848-2017). This product can solidify heavy metals well and can be well applied to the field of water conservancy projects to achieve in-situ and rapid disposal of sludge. In Comparative Examples 6 and 7, only one of the phosphorus-based enhancer and the aluminum-based enhancer was added, and the heavy metal solidification effect was significantly reduced, indicating that the synergistic effect of the phosphorus-based enhancer and the aluminum-based enhancer can achieve a good heavy metal solidification effect.

[0074] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An environmentally friendly sludge unfired building block, characterized in that: In terms of weight, the raw material components include 30-60 parts of sludge, 30-50 parts of binder, 5-20 parts of alkali activator, 2-10 parts of reinforcing agent and 10-20 parts of water. The binder includes blast furnace slag and fly ash, and the mass ratio of the blast furnace slag and fly ash is (0.5-5):

1. The reinforcing agent includes a phosphorus-based reinforcing agent and an aluminum-based reinforcing agent, and the mass ratio of the phosphorus-based reinforcing agent to the aluminum-based reinforcing agent is (0.8-1.2):

1.

2. The environmentally friendly sludge unburned building block according to claim 1 is characterized in that: The phosphorus-based enhancer is one or both of sodium tripolyphosphate and calcium dihydrogen phosphate.

3. The environmentally friendly sludge unburned building block according to claim 1 is characterized in that: The aluminum-based reinforcing agent includes one or both of sodium metaaluminate and aluminum phosphate.

4. The environmentally friendly sludge unburned building block according to claim 1 is characterized in that: Calculated by weight, the main chemical components of the sludge powder include: 35-55 parts of SiO2, 15-25 parts of Al2O3, 10-20 parts of LOI, 0-3 parts of K2O, 0-3 parts of CaO; and 0-3 parts of MgO.

5. The environmentally friendly sludge unburned building block according to claim 1 is characterized in that: The alkali activator includes a strong alkali activator and a weak alkali activator. The strong alkali activator includes one or both of sodium hydroxide and potassium hydroxide, and the weak alkali activator includes one or both of water glass and potassium silicate.

6. The environmentally friendly sludge unburned building block according to claim 1, characterized in that: The fly ash is Class F fly ash, and its main chemical components, calculated by weight, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.

7. The environmentally friendly sludge unburned building block according to claim 1 is characterized in that: The blast furnace slag is S95 grade powder, and its main chemical components include, by weight: 30-50 parts of CaO, 25-35 parts of SiO2, 10-20 parts of Al2O3, and 5-10 parts of MgO.

8. The method for preparing the environmentally friendly sludge unburned building block according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Pretreatment of raw materials: remove impurities from the sludge slurry and dry it to a moisture content of less than 5% to obtain dried sludge, and grind, shrink and homogenize the dried sludge to obtain sludge; S2, mixing of raw materials: mixing the sludge in step S1 with blast furnace slag and fly ash to obtain a precursor; S3, preparation of blank: mixing the precursor in step S2 with water, a reinforcing agent and an alkaline activator to obtain a blank; S4, molding and curing: the blank obtained in step S3 is pressed into shape, and after demoulding, it is cured at a set temperature to obtain a building block.

9. The method for preparing the environmentally friendly sludge unfired blocks according to claim 8, characterized in that: The grinding conditions in step S1 are: a rotation speed of 600 to 1200 rpm and a grinding time of 0.5 to 6 minutes.

10. The method for preparing the environmentally friendly sludge unfired building blocks according to claim 8, characterized in that: The curing temperature in step S4 is 15°C to 90°C.

Citation Information

Patent Citations

  • Sludge baking-free brick and preparation method thereof

    CN103102133A

  • Reservoir sediment baking-free brick and preparation method thereof

    CN117185733A

  • Geopolymer prepared from industrial waste residue and its preparation method

    CN103693870A

  • River silt baking-free brick and preparation method thereof

    CN108516765A

  • Alkali excitation slag / fly ash anti-freezing permeable concrete and preparation method thereof

    CN109516733A